Utilization of Canistel (Pouteria campechiana) into Butter as a Vitamin A Supplement - Puspita, Dhanang; Rahardjo, Monika; Sanubari, Theresia Pratiwi Elingsetyo; Kurniawan, Yosia Agung (Study Program of Nutrition, Public Health Faculty, Institut Kesehatan Helvetia, 2018)
Canistel fruit (Pouteria campechiana) is one of the plants that originates from Central America. In Indonesia, canistel is rarely found and not utilized optimally. Canistel contains very high carotenoids which can be used as food coloring and vitamin A supplements. Butter from canistel is an effort to increase the nutritional and economic value of this fruit. Objectives; the purpose of this study was to use the canistel into butter and see the acceptance of the researchers. Method; the study was conducted in September 2018, at the Food Technology Food Process Laboratory, Faculty of Medicine and Health Sciences, Satya Wacana Christian University. This study uses laboratory experimental methods with various prescription formulations. Results; organoleptic test results obtained differences in color, aroma, taste, texture and overall from 3 variants butter. Butter from canistel showed a positive trend toward the acceptance of panelists. This product has good potential in the utilization of canistel into butter. Conclution; utilization of canistel in the development of food products can be used as a food diversification that is rich in nutrients as well as a good impact to help nutritional intake, especially of vitamin A.